A dynamic and interoperable communication framework for controlling the operations of wearable sensors in smart healthcare applications - Shakeel, Pethuraj Mohamed; Baskar, S.; Mohd Aboobaider, Burhanuddin; Kumar, Raubin; Sampath, Rajaram (Elsevier B.V., 2020)
In this manuscript, a dynamic and interoperable communication framework (DICF) for regulating the operations of wearable healthcare devices is introduced. The framework is responsible for monitoring, decision making and controlling the functionalities and operating time of the wearable sensors (WS) as a part of smart health care tracking applications. In this framework, the nature of the wireless sensing device and its intrinsic features are accounted to design a fully operative and automated seamless working of the sensing devices. The sensing devices operate in both autonomous and interconnected manner depending upon the sensed information and the observed body conditions of the patient. The frequency of operation and the time interval varies with the scheduled and random recommendations of the communication framework of the interconnected devices. The framework is designed to improve the interoperability of the devices acclimatized to adapt dynamic nature of different tracking healthcare applications to leverage its performance